Terahertz all metallic perfect absorber for refractive index sensing and glucose concentration detection. (1st January 2023) - Barzegar-Parizi, Saeedeh; Ebrahimi, Amir
Abstract: A metallic perfect electromagnetic absorber with a simple design at terahertz frequencies is presented in this paper. The designed absorber consists of two-dimensional arrays of square cavities terminated with a conducting layer acting as a back reflector. Through a proper design of the unit cell dimensions, a very narrow resonance band with perfect absorption amplitude is achieved at THz frequencies. The designed absorber shows 0.052% fractional bandwidth with more than 90% absorption around the center frequency of 0.4978 THz with a quality factor of Q = 1920. The proposed structure can be used as a sensor to detect the refractive index of different materials with a sensitivity of 0.32 THz per refractive index unit (THz/RIU) and normalized sensitivity of 0.64 (1/RIU) resulting in figure-of-Merit (FOM) of 1230 (1/RIU). The designed absorber has potential applications in identifying biological samples as well. The results show that the sensor can be used to detect glucose concentration with an average sensitivity of 2.6 (THz/(mol l −1 )).